Enhancing Scientific Problem-Solving of Grade 10 Students through Problem-Based Learning with Ethical Dilemmas - Piyatida Thaochalee; Prasart Nuangchalerm (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
The purposes of this research were 1) to compare the achievement after using problem-based learning with ethical dilemmas on genetic variation and biotechnology with the criteria of 70 percent, 2) to compare the problem solving in science of Grade 10 students after learned with problem-based learning with ethical dilemmas with the criteria of 70 percent, and 3) to study satisfaction with problem-based learning with ethical dilemmas on genetic variation and biotechnology. The sample used in this research were 38 of Grade 10 students in the academic year 2022. Data were analyzed using mean, percentage, standard deviation. and t-test. The results of the research were as follows 1) the achievement of Grade 10 students receiving problem-based learning with ethical dilemmas after learning was not different from the criterion of 70 percent at a statistical significance level of .05, 2) the scientific problem solving ability of Grade 10 students who received a problem-based learning with ethical dilemmas were not different from the criterion of 75 percent at a statistical significance level of .05, and 3) the students were satisfied with the problem-based learning with ethical dilemmas at the highest level.